A potential common role of the Jumonji C domain-containing 1A histone demethylase and chromatin remodeler ATRX in promoting colon cancer - Li, Xiaomeng (Oncol Lett, 2018)
Jumonji C domain-containing 1A (JMJD1A) is a histone demethylase and epigenetic regulator that has been implicated in cancer development. In the current study, its mRNA and protein expression was analyzed in human colorectal tumors. It was demonstrated that JMJD1A levels were increased and correlated with a more aggressive phenotype. Downregulation of JMJD1A in human HCT116 colorectal cancer cells caused negligible growth defects, but robustly decreased clonogenic activity. Transcriptome analysis revealed that JMJD1A downregulation led to multiple changes in HCT116 cells, including inhibition of MYC- and MYCN-regulated pathways and stimulation of the TP53 tumor suppressor response. One gene identified to be stimulated by JMJD1A was α-thalassemia/mental retardation syndrome X-linked (ATRX), which encodes for a chromatin remodeler. The JMJD1A protein, but not a catalytically inactive mutant, activated the ATRX gene promoter and JMJD1A also affected levels of dimethylation on lysine 9 of histone H3. Similar to JMJD1A, ATRX was significantly overexpressed in human colorectal tumors and correlated with increased disease recurrence and lethality. Furthermore, ATRX downregulation in HCT116 cells reduced their growth and clonogenic activity. Accordingly, upregulation of ATRX may represent one mechanism by which JMJD1A promotes colorectal cancer. In addition, the data presented in this study suggest that the current notion of ATRX as a tumor suppressor is incomplete and that ATRX might context dependently also function as a tumor promoter.